STUDENT’S ANXIETY TOWARD ENGLISH SPEAKING SKILL OF DESCRIPTIVE TEXT USING STORYTELLING - Aqila Nisfa Maulida; Pradnya Permanasari (STKIP Siliwangi, 2023)
This study aims to investigate students’ ability in speaking English and to find out the anxiety factors that influence students’ mastery in speaking English in the tenth graders of SMK Gondang in the academic year of 2022/2023.This study includes descriptive qualitative research with a case study approach. The data was collected by questionnaires, observation and test of students performance. Then, the data was analyzed through several steps such as data reduction, data display, and validity. The results of this study showed that the ability of the tenth graders of SMK Gondang in English speaking is not so good. It can be seen from the mean score of students’ speaking test was 31.62. In addition, the data also showed that the are two anxiety factors that influence students’ speaking skills namely internal factors and external factors. The internal factor such as a lack of confidence, anxiety, nervousness, worries, tension and, dizziness to practicing speaking English. While, the external factors are teachers, parents, friends, and also the environment. Those factors make some students reluctant to practice speaking English in their learning. Keywords: Anxiety, descriptive text, speaking skill